THE INFLUENCE OF ROLE-PLAY GAME ON STUDENTS' SPEAKING SKILL: A PRE-EXPERIMENTAL STUDY AT AN ISLAMIC JUNIOR HIGH SCHOOL - Hikmah Pravitasari; Lisda Fauziyah (Cirebon International Conference on Education and Economics Proceeding, 2024)
This research aims to investigate the influence of the role play game on student’s speaking skill. The study used a pre-experimental design with single-group pretest and post-test combined with self-assessment to determine whether role-playing instruction had a beneficial or detrimental impact on students' speaking ability. The population were twenty-eight students with twelve male and sixteen female students from the nineth grade of an Islamic Junior High School in Indonesia. The research instruments included field notes and oral speaking assessments. The researcher treated students with role-playing to help them become more proficient speakers. The pre and post test results, along with Microsoft Excel 2019, were used to confirm the validity and reliability test initially. The average post-test score was greater than the pre-test score, according to the study findings. 55.21 was the average pre-test score, while 80.77 was the average post-test score. Pre-test and post-test averages showed variation in vocabulary mastery growth rates among the students. The t-test had a p-value (sig-2-tailed) of 0.00, which is less than 0.05. According to this result, Ha was accepted and Ho was rejected. It can be concluded that the use of role-play and self-assessment at nineth grade of an Islamic Junior High School to teach speaking English has a positive influence to improves students' speaking mastery.